Community Participation In Tourism Development At Kacirebonan Palace - Sungkawa, Khaeril; Wachyudi, Sudiana (Jurnal Toursci, 2024)
Cirebon is a city in West Java which has 4 (four) palaces, one of which is the Kacirebonan palace which is used as a historical tourist attraction. This research aims to determine the form of community participation ini tourism development at the Kacirebonan Palace and to determine the level of community participation ini tourism development at the Kacirebonan Palace. The research uses a qualitative descriptive method, namely primary data as the data source ini this research which is obtained from interviews, observation, questionnaires and documentation. The analysis technique used is the Likert scale. The results of the research show 4 (four) achievements in the level of community participation in tourism development at the Kacirebonan Palace, namely planning, reaching a score of 72.03 percent, implementation reaching a score of 71.85 percent, evaluation/monitoring 70.74 percent, and utilization of results 64.81 percent. percent. The community participation score in tourism development is in the high category as evidenced by the combined score for the areas of participation averaging 69.93 percent, this proves that community participation ini tourism development at the Kacirebonan Palace is relatively high. However, there are still differences between the data in the field of planning participation, the results of the Group Discussion Forum showing that participation is still low and the results of the questionnaire showing that there is a high level of participation. The form of community participation at the Kacirebonan Palace can be seen from the planning process, namely being involved in deliberations and taking the initiative to submit opinions. In terms of implementation, the community participates by providing performances or attractions, providing tourism comfort facilities, becoming tour guides, becoming tourism actors, becoming souvenir and food traders, maintaining security, order, cleanliness and comfort of tourist locations, as well as promoting Kacirebonan Palace tourism. Judging from the participation in the utilization of the results, this can provide jobs for the community, increase people's income, and reduce social inequality. Regarding participation in the evaluation, the community provides assessments, and participates in evaluating, criticizing and providing suggestions for tourism development and tourism management policies.